ADAKAH RELEVAN PENAWARAN TAKAFUL MIKRO KEPADA WARGA EMAS BERSAMA JABATAN KEBAJIKAN MASYARAKAT (JKM)? Is It Relevant to Offer Microtakaful to the Elderly in Cooperation with the Department of Social Welfare (JKM)? - Kamal, Asiah; Sulaiman@Mohamad, Ahmad Azam; Mohamad, Mohammad Taqiuddin (Jurnal Syariah, 2019)
Malaysia is expected to reach an aged population by 2030. Currently, micro takaful under the â€œPerlindungan Tenangâ€ initiative, does not promote the participation of the elderly in line with the increasing life expectancy of the country. This is mainly due to the link between the high risk of age-related-illness. For the microtakaful offering segment, takaful operators should not expect immediate profit. Therefore, the study was conducted to look at collaboration opportunities between takaful operators and the Department of Social Welfare (JKM) by offering microtakaful to senior citizens in the country. Befittingly this collaboration has allowed for the government department, JKM, to provide direct service to senior citizens. Thus, field studies were conducted with JKM, takaful operators and the Central Bank of Malaysia (BNM). Interviews with JKM involved a group of senior citizens, and also members of the productive welfare and a sample of the community. Interviews with takaful operators included AIA Public Takaful in the Product Marketing Department, Prudential BSN Takaful under microtakaful and CSR Department and IKHLAS Takaful in the Bancatakaful Department. Interviews with BNM were conducted with the Islamic Banking and Takaful Department. The offering of microtakaful to senior citizens living in institutions under the JKM and senior citizens receiving financial assistance ie â€œBantuan Orang Tua (BOT)â€ is made possible through funds from zakat, waqf and CSR in the form of non-commercial microtakaful. Whereas senior citizens living in the community can be offered commercial microtakaful through community cooperation, Elderly Care Centres, both from NGOs and privately registered centres have been cooperating with JKM to describe the value and importance of increasing understanding as well awareness of microtakaful. At the same time, microtakaful schemes need to make product design improvements to be relevant and appropriate for senior citizens, especially in terms of target schemes and supply channels.